Real Estate Production in Contaminated Areas and its Contribution to the 2030 Agenda: Perception of Experts for the City of São Paulo - Ferreira, Rafael Franklin da Silva; Yoshikawa , Nestor Kenji; Kniess , Cláudia Terezinha; Nascimento , Ana Paula Branco do (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
Among the various challenges of urbanization, the relationship between environmental impacts and the difficulty of meeting the expansive demand for housing and commerce stands out. In this last aspect, the real estate sector’s interest in making properties with industrial history suitable for residential or commercial use is highlighted. This interest comes up against, however, the damage caused by industrial contamination. In the municipality of São Paulo and the metropolitan region, this is a reality that is well known by the real estate sector. Therefore, the potential of Management of Contaminated Area (GAC) in providing opportunities to the real estate market is highlighted. Along with revitalization, GAC can collaborate with the quality of life in metropolises, one of the main urban sustainability goals established by the United Nations 2030 Agenda. In this sense, the objective of this work was to analyze the benefits and challenges of contaminated areas for the real estate production sector in the city of São Paulo, relating these aspects to sustainable development. The perception of nine specialists from the public and private sectors was analyzed through semi-structured interviews. The remediation and decontamination of areas impacted by industrial activities promote the revitalization of areas, increasing the availability of properties with safe use and contributing to society. The benefits of investing in contaminated areas, performed by categorization of feelings, showed that 100% of respondents have a positive feeling. The interpretation of the experts’ responses regarding the risks of investing in contaminated areas, carried out by categorization of feelings, showed that 100% of respondents had a negative feeling. In the experts’ perception, several benefits of the GAC were identified aimed at urban sustainability and a lack of knowledge regarding the contributions of management to the SDGs and the 2030 Agenda goals. Despite this assessment, the responses allowed diagnosing six SDGs in which the revitalization and remediation of contaminated areas play a central role: SDG 3, 4, 11, 12 and 13.